Cerebral Oximetry During Cardiac Arrest: A Multicenter Study of Neurologic Outcomes and Survival*. Issue 9 (September 2016) - Parnia, Sam; Yang, Jie; Nguyen, Robert; Ahn, Anna; Zhu, Jiawen; Inigo-Santiago, Loren; Nasir, Asad; Golder, Kim; Ravishankar, Shreyas; Bartlett, Pauline; Xu, Jianjin; Pogson, David; et al.
Abstract : Objectives: Cardiac arrest is associated with morbidity and mortality because of cerebral ischemia. Therefore, we tested the hypothesis that higher regional cerebral oxygenation during resuscitation is associated with improved return of spontaneous circulation, survival, and neurologic outcomes at hospital discharge. We further examined the validity of regional cerebral oxygenation as a test to predict these outcomes. Design: Multicenter prospective study of in-hospital cardiac arrest. Setting: Five medical centers in the United States and the United Kingdom. Patients: Inclusion criteria are as follows: in-hospital cardiac arrest, age 18 years old or older, and prolonged cardiopulmonary resuscitation greater than or equal to 5 minutes. Patients were recruited consecutively during working hours between August 2011 and September 2014. Survival with a favorable neurologic outcome was defined as a cerebral performance category 1–2. Interventions: Cerebral oximetry monitoring. Measurements and Main Results: Among 504 in-hospital cardiac arrest events, 183 (36%) met inclusion criteria. Overall, 62 of 183 (33.9%) achieved return of spontaneous circulation, whereas 13 of 183 (7.1%) achieved cerebral performance category 1–2 at discharge. Higher mean ± SD regional cerebral oxygenation was associated with return of spontaneous circulation versus no return of spontaneous circulation (51.8% ± 11.2% vs 40.9% ± 12.3%) and cerebral performance category 1–2 versus cerebral performance category 3–5 (56.1% ± 10.0% vs 43.8% ± 12.8%) (both p < 0.001). Mean regional cerebral oxygenation during the last 5 minutes of cardiopulmonary resuscitation best predicted the return of spontaneous circulation (area under the curve, 0.76; 95% CI, 0.69–0.83); regional cerebral oxygenation greater than or equal to 25% provided 100% sensitivity (95% CI, 94–100) and 100% negative predictive value (95% CI, 79–100); regional cerebral oxygenation greater than or equal to 65% provided 99% specificity (95% CI, 95–100) and 93% positive predictive value (95% CI, 66–100) for return of spontaneous circulation. Time with regional cerebral oxygenation greater than 50% during cardiopulmonary resuscitation best predicted cerebral performance category 1–2 (area under the curve, 0.79; 95% CI, 0.70–0.88). Specifically, greater than or equal to 60% cardiopulmonary resuscitation time with regional cerebral oxygenation greater than 50% provided 77% sensitivity (95% CI, :46–95), 72% specificity (95% CI, 65–79), and 98% negative predictive value (95% CI, 93–100) for cerebral performance category 1–2. Conclusions: Cerebral oximetry allows real-time, noninvasive cerebral oxygenation monitoring during cardiopulmonary resuscitation. Higher cerebral oxygenation during cardiopulmonary resuscitation is associated with return of spontaneous circulation and neurologically favorable survival to hospital discharge. Achieving higher regional cerebral oxygenation during resuscitation may optimize the chances of cardiac arrest favorable outcomes.